Detection of DNA crosslinks in peripheral lymphocytes isolated from patients treated with platinum derivates using modified comet assay - Fikrova, P; Stetina, R; Hrnciarik, M; Rehacek, V; Jost, P; Hronek, M; Zadak, Z (Neoplasma, 2013)
Platinum-based chemotherapeutic agents induce the formation of crosslinks in DNA, which are accepted as being responsible for the cytotoxicity of these agents. In this study, we used a modification of the alkaline comet assay for detection of the presence of DNA crosslinks in vitro caused by cisplatin, and in peripheral lymphocytes of patients with non-small cell lung carcinoma undergoing chemotherapy with platinum derivatives. The comet technique modified for the detection of DNA crosslinks was calibrated in vitro by treating HeLa cells and human lymphocytes from healthy donors with different concentrations of cisplatin. A cisplatin dose-dependent formation of DNA crosslinks was observed in in vitro measurements using 10-200 µM concentrations of cisplatin. Lymphocytes from cancer patients were also assayed for the formation and repair of DNA crosslinks. Evidence of crosslink formation and repair was observed in peripheral blood lymphocytes of all cancer patients in this study, although some inter-individual differences were observed in the response to chemotherapy and in repair of DNA crosslinks. We propose that monitoring the number of DNA crosslinks in peripheral blood lymphocytes might be a quick and sensitive method for monitoring a patient's sensitivity to this agent. Modification of the method by incubation of analysed cells with styrene oxide before crosslink analysis by comet assay extends the use of the method also to laboratories which have no facilities to use ionizing irradiation for introducing DNA breaks into the cells.
Keywords: kometový test; senioři; Aged; DNA Damage; Lung Neoplasms; Male; lidé; lidé středního věku; Humans; Carcinoma, Non-Small-Cell Lung; Middle Aged; protinádorové látky; Antineoplastic Agents; Lymphocytes; poškození DNA; nádory plic; HeLa buňky; mužské pohlaví; HeLa Cells; nemalobuněčný karcinom plic; cisplatina; Cisplatin; ženské pohlaví; Female; Comet Assay; lymfocyty